The Effects of Application of Erythrina bruci Biomass and Inorganic Fertilizers On Wheat Productivity in Southwestern Ethiopia. - Zelalem Addis Musse (Department of Agronomy and Horticulture, IPB University, 2023)
Soil fertility depletion is emerging as a serious challenge causing low crop yields and food insecurity in Ethiopia. An experiment was conducted in two cropping seasons 2016 to 2018 to investigate the effects of the application of Erythrina biomass and nitrogen fertilizer on soil properties and wheat yields in southwestern Ethiopia. Treatments were the recommended N and P fertilizers, 50% of the standard rate of Erythrina + 50% of the recommended N, 25% Erythrina + 75% N, 75% of the standard rate of Erythrina + 25% of the standard rate of N, 100% of the standard rate of Erythrina, and 50% of the standard rate of Erythrina, and without fertilizer as the control. The experiment was arranged in a randomized complete block design with three replications. Application of Erythrina and nitrogen fertilizer increased soil organic carbon (OC), total nitrogen (TN), and cation exchange capacity (CEC) compared to before fertilizer application or the control. Plots amended with 25% Erythrina + 75% of the recommended N provided the highest above ground biomass (8.98 t.ha-1) and grain yield (3.453 t.ha-1) and it was higher than the 100% chemical fertilizer treatment. Conversely, the lowest above ground biomass (5.44 t.ha-1) and grain yields (1.958 t.ha-1) were obtained from the control. Our study demonstrated that an integrated nutrient management which combines organic and chemical fertilizer can improve soil properties and increase wheat yield in the highlands of southwestern Ethiopia.